2014
DOI: 10.1021/jf404278q
|View full text |Cite
|
Sign up to set email alerts
|

Hemp (Cannabis sativa L.) Seed Oil: Analytical and Phytochemical Characterization of the Unsaponifiable Fraction

Abstract: Non-drug varieties of Cannabis sativa L., collectively namely as "hemp", have been an interesting source of food, fiber, and medicine for thousands of years. The ever-increasing demand for vegetables oils has made it essential to characterize additional vegetable oil through innovative uses of its components. The lipid profile showed that linoleic (55%), α-linolenic (16%), and oleic (11%) were the most abundant fatty acids. A yield (1.84-1.92%) of unsaponifiable matter was obtained, and the most interesting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 41 publications
7
100
2
1
Order By: Relevance
“…The UF, about 1.5-2% of the oils, is an important source of interesting minor compounds. 7,8 As part of ongoing investigations on bioactive secondary plant metabolites in medicinal and food plants, our aim of the present study was to conduct a detailed analysis to establish the anti-oxidant and anti-inflammatory effects for this valuable oilseed crop.…”
Section: Introductionmentioning
confidence: 99%
“…The UF, about 1.5-2% of the oils, is an important source of interesting minor compounds. 7,8 As part of ongoing investigations on bioactive secondary plant metabolites in medicinal and food plants, our aim of the present study was to conduct a detailed analysis to establish the anti-oxidant and anti-inflammatory effects for this valuable oilseed crop.…”
Section: Introductionmentioning
confidence: 99%
“…Tocopherols are the lipid soluble compounds found in minor quantities in the seed oils. They are natural antioxidants and have free radical scavenging ability involving tocopherol-tocopheryl semiquinone redox system 32 . γ-tocopherol 741.64 mg/kg of oil is the major tocopherol found in the B. arvensis seed oil followed by β-tocopherol 32.84 mg/kg of the oil Table 2 .…”
Section: Tocopherols Contentmentioning
confidence: 99%
“…γ-tocopherol 741.64 mg/kg of oil is the major tocopherol found in the B. arvensis seed oil followed by β-tocopherol 32.84 mg/kg of the oil Table 2 . Other vegetable oils such as rape seed oil, hemp oil and sacha inchi seed oil also have γ-tocopherols as a predominant tocopherol isomer 32,33 . Earlier reports showed that the antioxidant capacity of tocopherol isomers decreases in the order of γ δ β α-tocopherol 33 .…”
Section: Tocopherols Contentmentioning
confidence: 99%
“…Finola and Uso31 oils have the richest g-linolenic acid (5-6%). A yield (1.84-1.92%) of unsaponifiable matter was obtained from a Spain HO (Montserrat-de la Paz et al, 2014), and the most interesting compounds were b-sitosterol (1905.00 AE 59.27 mg/kg of oil), campesterol (505.69 AE 32.04 mg/kg), phytol (167.59 AE 1.81 mg/kg), cycloartenol (90.55 AE 3.44 mg/kg), and g-tocopherol (73.38 AE 2.86 mg/100 g). These oils can be used to produce essential fatty acid (EFA) dietary supplements high in o-6 and o-3.…”
Section: Hemp Seed Oilmentioning
confidence: 99%